Euthanizing zebrafish legally in Europe: Are the approved methods of euthanizing zebrafish appropriate to research reality and animal welfare?. (18th October 2016) - Valentim, Ana M; van Eeden, Fredericus J; Strähle, Uwe; Olsson, I Anna S
Abstract : As zebrafish are becoming an increasingly important model organism in biomedical research, the approved methods of euthanizing fish should be expanded to improve both animal welfare and the quality of research.